Extrauterine Placental Site Trophoblastic Tumor Involving the Vagina. (May 2017) - Gupta, Mayank; Gnanasekaran, Kiruthiga K.; Manojkumar, Ramani; Thomas, Anitha; Sebastian, Ajit
Abstract : Very few cases of placental site trophoblastic tumor (PSTT) primarily involving extrauterine sites have been reported to date. We report a case of a 29-year-old female who presented with a vaginal nodule 9 months after delivery at an outside hospital which was initially diagnosed as a poorly differentiated squamous cell carcinoma. Subsequently she was referred to our institute, and on the basis of histology, mildly elevated serum β-HCG level, and immunohistochemistry, PSTT was diagnosed. After the completion of chemotherapy, the vaginal nodule completely regressed and serum β-hCG returned to baseline. Her follow-up has been unremarkable. This case highlights the importance of the fact that PSTT can be easily misdiagnosed at extrauterine sites in the absence of proper clinical, histologic, and immunohistochemical correlation.